Handbook marine model organisms in experimental biology : established and emerging - Schierwater, B. (CRC Press, 2022)
"Much of our biological and biomedical knowledge derives from studying marine model systems. In this new handbook world-leading experts describe the cutting-edge work and potential for their unique model system. This will be a gold mine for students and scientists from all fields of life sciences"--
Includes bibliographical references and index.
Keywords: Marine organisms; Biological models; Biology, Experimental; Biological systems